An electrophysiological signature of unconscious recognition memory - Voss, Joel L; Paller, Ken A (Nature neuroscience, 2009)
Explicit memory is linked to conscious awareness of memory retrieval, whereas implicit memory can guide behavior without conscious awareness of memory retrieval. Here, the authors demonstrate recognition memory without awareness of the retrieval. ERP measures differentiated between implicit and explicit recognition. Contradicting the common assumption that accurate recognition reflects explicit-memory processing, we provide evidence for recognition lacking two hallmark explicit-memory features: awareness of memory retrieval and facilitation by attentive encoding. Kaleidoscope images were encoded in conjunction with an attentional diversion and were subsequently recognized more accurately than those encoded without diversion. Confidence in recognition was superior following attentive encoding, although recognition was markedly accurate when people claimed to be unaware of memory retrieval. This 'implicit recognition' was associated with frontal-occipital negative brain potentials at 200–400 ms post-stimulus-onset, which were spatially and temporally distinct from positive brain potentials corresponding to explicit recollection and familiarity. This dissociation between behavioral and electrophysiological characteristics of 'implicit recognition' versus explicit recognition indicates that a neurocognitive mechanism with properties similar to those that produce implicit memory can be operative in standard recognition tests. People can accurately discriminate repeat stimuli from new stimuli without necessarily knowing it.